Simultaneous Electrochemical Detection of Multiple Heavy-Metal Ions Based on Furfural/Reduced Graphene Oxide Composites. Issue 12 (16th December 2021) - Xu, Xiaoyun; Lv, Xiaoyi; Tan, Fei; Li, Yanping; Geng, Chao; Cui, Bo; Fang, Yishan
Abstract : An efficient and sensitive electrochemical sensor for simultaneous detection of heavy metal ions was developed based on furfural/reduced graphene oxide composites (FF/RGO). The preparation of FF/RGO were performed through a one-step high-pressure assisted hydrothermal treatment, which is recommended as a green, convenient, and efficient way for the reduction of graphene oxide and the production of FF/RGO composites. RGO not only serves as the skeleton for furfural loading but also improves the conductivity of the composites in the matrix. FF/RGO with large specific surface area and abundant oxygen-containing functional groups was used to provide more binding sites for the effificient adsorption of heavy-metal ions due to the interaction between hydrophilic groups (–COOH, –OH, and –CHO) and metal cations. The developed sensor showed identifiable electrochemical response toward the heavy metal ions separately and simultaneously, exhibiting superior stability, outstanding sensitivity, selectivity and excellent analytical performance. Impressively, the sensor developed in this experiment has been successfully applied to the simultaneous determination of various heavy metal ions in actual samples, which has definitely exhibited a promising prospect in practical application.